Coating of Nanotube Ti6Al4V Alloy with Hydroxyapatite-Chitosan-Polyvinyl Alcohol Composite - Charlena Charlena; Tetty Kemala; Ravena Ravena (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Hydroxyapatite (HAp) can be applied as a bone implant material. HAp was composited with chitosan and polyvinyl alcohol (PVA) and coated to Ti6Al4V to improve its biocompatibility. The composite HAp-chitosan-PVA coated to anodized and unanodized Ti6Al4V. Modification of the Ti6Al4V surface by anodizing was done using a 20 V voltage. The Ti6Al4V metal alloy was coated with a composite using the electrophoretic deposition (EPD) method with a voltage of 80 V. The coated composites in Ti6Al4V nanotubes and non-nanotubes were characterized by Scanning Electron Microscope (SEM), X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR), corrosion test with potentiostat, and in vitro bioactivity test with Atomic Absorption Spectroscopy (AAS). The XRD results showed a distinctive peak indicating that the composite comprises HAp and Ti. The SEM Ti6Al4V nanotube results show a pore size of 24 nm. The FTIR results show that there were functional groups of HAp, chitosan, and PVA. The corrosion rate on Ti6Al4V nanotubes without coating was greater than with coating. The In vitro bioactivity test showed that the decrease of Ca2+ Ti6Al4V nanotube concentration was faster compared to non-nanotube Ti6Al4V.